Culture of the Aspirated Coronary Thromboembulus Specimen: A Peculiar Diagnostic Method for Infective Endocarditis - Massimo Slavich; Andrea Fisicaro; Eustachio Agricola; Giovanni Coppi; Carlo Ballarotto; Alberto Margonato (Case Reports in Medicine)
A 69-year-old man was admitted to our hospital for persistent fever, myalgias, articular pain, headache, and hypoaesthesia of the scalp. The clinical scenario was typical for giant-cell arteritis. During hospital stay, patient developed fugax amaurosis, stroke, and acute coronary syndrome. The definitive diagnosis of infective endocarditis, supported by transesophageal echocardiography, was confirmed only by culturing the material obtained during angiography and coronary thromboaspiration.